Управление безопасностью объектов атомной энергетики согласно концепции виртуальной аварии - Пампуро, В.И. (Видавничий дім "Академперіодика" НАН України, 2007)
The article substantiates the control over the safety of nuclear engineering objects (including NPPs, surface and underground repositories) according to the conception of virtual accident. The comprehensive analysis of the mistake of the probabilistic model of the time interval between heavy accidents is given. The step-by-step control over the safety with the use of some states of an object is grounded.